Drawn from life : issues and themes in animated documentary cinema - Murray, Jonathan, 1973-; Ehrlich, Nea (Edinburgh studies in film and intermediality., 2019)
Drawn from life', a multidisciplinary anthology, introduces readers to a diverse range of filmmakers past and present who use the animated image as a documentary tool. From early cinema to present-day scientific research, military uses, digital art and gaming, this original volume casts new light on the capacity of the moving image to act as a record of the world around us.